2013
DOI: 10.3109/00365513.2013.860615
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin (NGAL) for the early detection of contrast-induced nephropathy after percutaneous coronary intervention

Abstract: Urinary NGAL is a biomarker for predicting CI-AKI when measured 1 day after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…Despite published data demonstrating that urinary neutrophil gelatinase-associated lipocalin (U-NGAL) is a real-time marker [31], our result showed that there was a significant difference between the serum and urinary NGAL biomarker levels after administration of CP at a high dose of 50 mg/m 2 , which was seen at the highest range of NGAL gene expression at urinary; in agreement with this finding, Liebetrau et al suggested that the urinary NGAL as a marker of tubular damage depends on these parameters as well [32]. The present study demonstrated that U-NGAL compared with serum NGAL is a major biomarker for the early risk stratification of ACRI after CP chemotherapy and is superior to prognosis for the early detection of kidney injuries.…”
Section: Discussionsupporting
confidence: 93%
“…Despite published data demonstrating that urinary neutrophil gelatinase-associated lipocalin (U-NGAL) is a real-time marker [31], our result showed that there was a significant difference between the serum and urinary NGAL biomarker levels after administration of CP at a high dose of 50 mg/m 2 , which was seen at the highest range of NGAL gene expression at urinary; in agreement with this finding, Liebetrau et al suggested that the urinary NGAL as a marker of tubular damage depends on these parameters as well [32]. The present study demonstrated that U-NGAL compared with serum NGAL is a major biomarker for the early risk stratification of ACRI after CP chemotherapy and is superior to prognosis for the early detection of kidney injuries.…”
Section: Discussionsupporting
confidence: 93%
“…In SHRs with CI-AKI, the area under the receiver operating characteristic curve (AUROC) value of NGAL is 0.73, which is accepted as a value of failure [6] . In contrast, in humans with CI-AKI, 4 of 8 studies showed an excellent value (0.93-1.0) [39][40][41][42] , 2 of 8 studies showed a good value of NGAL (0.83-0.84) [43,44], and 2 of 8 studies showed a poor value of NGAL (0.63-0.68) [29,45] . In CKD patients undergoing elective coronary angiography with contrast, postprocedural NGAL increases from baseline in each stage of CKD [46] .…”
Section: Similar Pathogenesis Of Ed and Asymmetric Dimethylarginine Imentioning
confidence: 93%
“…Haase et al (28) analyzed data from 191 patients in 3 studies and found that when urinary NGAL is measured within 6 hours after contrast medium administration, it has better sensitivity than serum creatinine alone for acute kidney injury detection. Moreover, recent studies and a meta-analysis have demonstrated the role of serum and urinary NGAL in the prediction of CIN (15,16,(29)(30)(31)(32)(33)(34)(35)(36) and, although this biomarker has also been reported to have a low sensitivity in predicting CIN in specific settings, such as ACS (37), a previous study also suggested that it can also predict the severity of CIN (38).…”
Section: Discussionmentioning
confidence: 99%